Ethnomedicinal appraisal of the medicinal flora among the sub-alpine and alpine Iindigenous communities of Palas Valley Kohistan, Northern Pakistan - Kayani, Sadaf; Ahmad, Mushtaq; Gillani, Syed Waseem; Muhammad Manzoor; Rehman, Fazal Ur; Jabeen, Shaista; Butt, Maryam Akram; Babar, Choudhary Muhammad; Shah, Syed Awais Hussain (Ethnobotany Research and Applications, 2024)
Background: The contemporary research was conducted to explore the ethnomedicinal potential of wild flora exploited by the indigenous communities of Palas valley of Kohistan, Northern Pakistan. It constitutes an important contribution to the knowledge of biological resources used for treatment of ailments through traditional practices. Methods: Rapid appraisal approach (RAA), semi-structured interviews, and personal monitoring, group discussion with community and interviews with herbalist were carried out to obtain information of ethnomedicinal values. The data gathered from the site was examined using quantitative ethnobotanical indices, viz., informant consensus factor (ICF), use value (UV), and Fidelity level (FL).Results: The current study recorded 102 plants with medicinal values which belong to 48 families which were described by 243 informants of area (female informants 87, male informants 137 and herbal specialists 19). Family Rosaceae was the abundantly utilized family with 10 reported plants species with medicinal values. Wild herbs were the prime source of herbal medicines (40.19%), followed by wild shrubs (39.21%). Leaves (23%) were the most frequently used plant part, followed by roots (12%) and whole plants (10%), and decoctions were the most preferred preparations. Conclusions: Indigenous herbal medicines play a major role in the system of local healthcare of Palas valley. The native people prefer to utilize the traditional preparations of herbal plants as remedies for various diseases. The plant with greater UV and FL% is playing vital role in the basic healthcare system. This outcome suggests further phytochemical studies to discover novel biological compounds for the exploration of drugs in future. Keywords: Ethnomedicinal appraisal, Subalpine, Alpine, Indigenous communities, Palas valley